Pengembangan Instrumen Berpikir Kritis : Tutor Identifikasi Berfikir Kritis - Adisti Yuliastri; Rian Vebrianto; Annisa Fazila Sabrina Damanik (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2023)
Research instrument is an important factor in research where the truth of research results lies and determines conclusions. The aim of this study is to review valid, consistent and reliable instruments for critical thinking. In this study, critical thinking consists of five construct, namely : (1) Provide a simple explanation; (2) Development of basic skills; (3) Summary; (4) Provide a more detailed explanation; and (5) Deciding the next strategy. Designed as a survey research, it involved 50 respondents consisting of 3 experts/lectures, 5 teacher and 42 students who were selected by stratified sampling technique and random chance. Data were analyzed using SPSS Version 23.00 for Windows to test internal concistency using Cronbach Alpha. The results showed that all items in the questionnaire were valid and reliable, withan average high Cronbach’s Alpha realibility score (0.897 > 0.6) and each statement had a high score (0.784 to 0.890). Therefore, these numbers indicate that this study has developed a qualitative critical thinking toolkit. Kata kunci: Berpikir Kritis, Instrumen, Tutor